2017
DOI: 10.1161/strokeaha.116.015042
|View full text |Cite
|
Sign up to set email alerts
|

YAMATO Study (Tissue-Type Plasminogen Activator and Edaravone Combination Therapy)

Abstract: T he goal of hyperacute stroke therapy is to recanalize the occlusive artery as soon as possible. Once a cerebral artery is occluded, blood and oxygen supply rapidly decrease and the neuron, glia cell, and vascular elements are immediately impaired, which leads to permanent damage.1 Early spontaneous recanalization occurs and rescues the brain tissue from ischemia, which is the underlying cause of most transient ischemic attacks. Over the past 2 decades, intravenous Background and Purpose-We investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…This study showed that combination therapy accelerated recanalization and reduced the incidence of cerebral hemorrhage ( 214 ). The YAMATO study was then carried out to determine whether early (vs. late) edaravone infusion promoted early recanalization and reduced complications, but failed to show any difference in outcome with either paradigm ( 215 ).…”
Section: Anti-inflammatory Treatment Combined With Acute Revascularizmentioning
confidence: 99%
“…This study showed that combination therapy accelerated recanalization and reduced the incidence of cerebral hemorrhage ( 214 ). The YAMATO study was then carried out to determine whether early (vs. late) edaravone infusion promoted early recanalization and reduced complications, but failed to show any difference in outcome with either paradigm ( 215 ).…”
Section: Anti-inflammatory Treatment Combined With Acute Revascularizmentioning
confidence: 99%
“…Investigators in the Tissue-Type Plasminogen Activator and Edaravone Combination Therapy (YAMATO) study [60] attempted to assess whether edaravone administration before or during tPA therapy can expedite the recanalization of occluded arteries. This was a multicenter, prospective, randomized, and open-label study.…”
Section: Drugs That Have Shown Potential Benefits In Clinical Studiesmentioning
confidence: 99%
“…Метою нейропротекторної терапії є подовження періоду терапевтичного вікна, що дозволяє розширити можливості для проведення тромболітичної терапії, зменшити розміри інфаркту мозку та захистити церебральну паренхіму від реперфузійного ушкодження [7].…”
Section: оригінальне дослідженняunclassified
“…У зв'язку із цим перспективним напрямом лікування ішемічного інсульту може вважатися застосування фармакологічних препаратів, здатних включитися в систему захисту мозку від окислювального стресу, запобігати вільнорадикальним процесам і забезпечувати антиоксидантну дію. Утім, попри очевидну доцільність антиоксидантної терапії в разі гіпоксії та ішемії мозку і наявність численних експериментальних доказів її ефективності, наразі зберігається дефіцит доступних для широкої клінічної практики антиоксидантних засобів, до того ж терміни і схеми їх застосування остаточно не визначені [3,[4][5][6][7].…”
Section: оригінальне дослідженняunclassified